A neuroscientific perspective of consumer responses to retail greenery. Issue 15 (10th December 2019) - Rosenbaum, Mark S.; Ramírez, Germán Contreras; Matos, Nancy
ABSTRACT: This research assesses consumers' neural activation in response to natural elements, present in a lifestyle center, as measured by electroencephalography (EEG). The study builds on previous research that demonstrates not only consumer preferences for greenery in shopping areas but also the stress-reducing, or restorative, health benefits that consumers may receive by spending time in green areas. This study extends these findings by offering insights derived from consumer neural responses. Participants recruited in a shopping mall viewed a video that showed a customer journey through a lifestyle center that either featured biophilic design or did not. Participants wore a mobile Emotiv EPOC+ EEG headset to record neural responses to the video; their responses reflect six emotional and sub-conscious dimensions. The data indicate that biophilia design elements stimulate consumers' neural activities associated with excitement, interest, decreased stress, engagement, attention, and relaxation, thus explaining why shoppers tend to respond positively to retail greenery.